Ironmaking and Steelmaking - Li, Zushu (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Steel is a critical material in our societies and will remain an important one for a long time into the future. In the last two decades, the world steel industry has gone through drastic changes and this is predicted to continue in the future. The Asian countries (e.g. China, India) have been dominant in the production of steel creating global over-capacity, while the steel industry in the developed countries have made tremendous efforts to reinforce its global leadership in process technology and product development, and remain sustainable and competitive. The global steel industry is also facing various grand challenges in strict environmental regulation, new energy and materials sources, and ever-increasing customer requirements for high quality steel products, which has been addressed accordingly by the global iron and steel community. This Special Issue, "Ironmaking and Steelmaking", released by the journal Metals, published 33 high quality articles from the international iron and steel community, covering the state-of-the-art of the ironmaking and steelmaking processes. This includes fundamental understanding, experimental investigation, pilot plant trials, industrial applications and big data utilization in the improvement and optimization of existing processes, and research and development in transformative technologies. It is hoped that the creation of this special issue as a scientific platform will help drive the iron and steel community to build a sustainable steel industry.